2017
DOI: 10.1167/iovs.16-20853
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Bacteria Flora of Glaucoma Patients During Long-Term Administration of Prostaglandin Analog Drops

Abstract: PURPOSE.To investigate the effects of the long-term use of prostaglandin analogs for glaucoma treatment on the indigenous flora of the conjunctiva.METHODS. Bacterial isolates were collected from the conjunctival sacs of 68 patients at Miyata Eye Hospital from February to September 2014, who had been receiving continuous monotherapy with prostaglandin analogs for glaucoma for at least 1 year. Minimum inhibitory concentrations of levofloxacin, gatifloxacin, moxifloxacin, cefmenoxime, tobramycin, chloramphenicol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Although our cohort of patients did not demonstrate a difference in the microbial composition between individuals using topical medications, other studies do suggest that long-term use of topical medications does affect the OSM. 24 It is possible that the individuals had not used the medications for a sufficient length of time to induce change and/or that our cohort was not large enough to fully evaluate this finding. Additionally, our patients often had ocular morbidities and/or topical ocular medication use, which is also not reflective of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Although our cohort of patients did not demonstrate a difference in the microbial composition between individuals using topical medications, other studies do suggest that long-term use of topical medications does affect the OSM. 24 It is possible that the individuals had not used the medications for a sufficient length of time to induce change and/or that our cohort was not large enough to fully evaluate this finding. Additionally, our patients often had ocular morbidities and/or topical ocular medication use, which is also not reflective of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a number of studies reporting the presence of bacteria in the conjunctival sac, these works were conducted in patients suffering from various eye diseases, such as Stevens -Johnson syndrome and cataracts [5,6]. These works show that the microbial flora may change as a result of surgery [7,8], use of antibiotics [9] and even seasonal change. For instance, it was found that conjunctival bacteria in patients undergoing cataract surgery presented a seasonal prevalence pattern where different bacteria were identified in different seasons [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported that methicillin-resistant S. epidermidis occurred more frequently on the ocular surface of glaucoma patients subjected to the long-term use of Xa compared to that for subjects treated with Tz. 10 These isolates were obtained from the indigenous flora of the conjunctiva of glaucoma patients treated with prostaglandin analog monotherapy for at least 1 year. In the current study, we analyzed these S. epidermidis isolate stocks and found that those obtained from the ocular surface of glaucoma patients under Xa treatment exhibited resistance to BAC as indicated by higher MIC values ( Table 2 ), and, especially, methicillin-resistant isolates were significantly resistant to BAC.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that methicillin-resistant Staphylococcus epidermidis (MRSE) was isolated more frequently in patients treated with 0.005% latanoprost (Xalatan [Xa]; Pfizer, Inc., New York, NY), which contains BAC, than in patients treated with 0.004% travoprost (Travatan Z [Tz]; Alcon Japan Co. Ltd., Tokyo, Japan), which does not contain BAC. 10 In the current study, we aimed to clarify the factors related to the methicillin susceptibility of S. epidermidis in the conjunctival flora. Specifically, we analyzed the susceptibility of S. epidermidis isolated in our previous report 10 to main prostaglandin agents and BAC and examined whether the isolated S. epidermidis contained the qacA/B and qacC/smr genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation